1997
DOI: 10.1111/j.1365-2044.1997.213-az0348.x
|View full text |Cite
|
Sign up to set email alerts
|

Staff stress on the intensive care unit: a comparison of doctors and nurses

Abstract: SummaryWorking on an intensive care unit is perceived as stressful. This study investigated occupational stress in staff working on an intensive care unit using the occupational stress indicator. Questionnaires were given to all intensive care staff; the replies were then analysed and compared with normative data. The response rate was 62%. Intensive care unit staff found aspects of their job relating to career and achievement and organisational design and structure more stressful than a normal working populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 11 publications
0
18
0
4
Order By: Relevance
“…The high percentage of stress that is reported by both genders in the present study is evidence of the heavy workload that is experienced by the physicians in NGHA. On the contrary, a study done in the United Kingdom concluded that both age and sex of medical doctors were not significant when measuring stress, which is associated with TMD (Goodfellow, Varnam, Rees, & Shelly, ; Sardar, ). Nonetheless, the same study concluded that the job itself for a physician is not the cause of stress.…”
Section: Discussionmentioning
confidence: 99%
“…The high percentage of stress that is reported by both genders in the present study is evidence of the heavy workload that is experienced by the physicians in NGHA. On the contrary, a study done in the United Kingdom concluded that both age and sex of medical doctors were not significant when measuring stress, which is associated with TMD (Goodfellow, Varnam, Rees, & Shelly, ; Sardar, ). Nonetheless, the same study concluded that the job itself for a physician is not the cause of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies in the literature reported that burnout scores were higher among female compared to male physicians, some others did not demonstrate any significant effect of gender (18,20,21,26,27). Additionally, some studies reported that internet use was more common among men and their addiction scores were higher, while there are also studies reporting no significant difference (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies and differs from the medical profession. Goodfellow et al identified stressors within the intensive care unit (ICU) and noted that ICU nurses had significantly greater pressure from lack of career and achievement and much lower job satisfaction that junior and senior medical staff 6 . This was supported by their comments on ways to improve their jobs that included better education, increased decision making and better career pathways.…”
Section: Discussionmentioning
confidence: 99%